A multiyear estimate of methane fluxes in Alaska from CARVE atmospheric observations. Issue 10 (9th October 2016) - Miller, Scot M.; Miller, Charles E.; Commane, Roisin; Chang, Rachel Y.‐W.; Dinardo, Steven J.; Henderson, John M.; Karion, Anna; Lindaas, Jakob; Melton, Joe R.; Miller, John B.; Sweeney, Colm; Wofsy, Steven C.; et al.
Abstract: Methane (CH4 ) fluxes from Alaska and other arctic regions may be sensitive to thawing permafrost and future climate change, but estimates of both current and future fluxes from the region are uncertain. This study estimates CH4 fluxes across Alaska for 2012–2014 using aircraft observations from the Carbon in Arctic Reservoirs Vulnerability Experiment (CARVE) and a geostatistical inverse model (GIM). We find that a simple flux model based on a daily soil temperature map and a static map of wetland extent reproduces the atmospheric CH4 observations at the statewide, multiyear scale more effectively than global‐scale process‐based models. This result points to a simple and effective way of representing CH4 fluxes across Alaska. It further suggests that process‐based models can improve their representation of key processes and that more complex processes included in these models cannot be evaluated given the information content of available atmospheric CH4 observations. In addition, we find that CH4 emissions from the North Slope of Alaska account for 24% of the total statewide flux of 1.74 ± 0.26 Tg CH4 (for May–October). Global‐scale process models only attribute an average of 3% of the total flux to this region. This mismatch occurs for two reasons: process models likely underestimate wetland extent in regions without visible surface water, and these models prematurely shut down CH4 fluxes at soil temperatures near 0°C. Lastly, we find that the seasonality of CH4 fluxes varied during 2012–2014 but that total emissions did not differ significantly among years, despite substantial differences in soil temperature and precipitation. Key Points: A simple model of soil temperature and wetland distribution can reproduce patterns in atmospheric CH4 observations The largest CH4 fluxes in Alaska occur in lowland tundra—in the southwest (e.g., Yukon‐Kuskokwim Delta) and North Slope We do not find evidence for large year‐to‐year variability in total CH4 fluxes from Alaska